EPITAXIAL LATERAL OVERGROWTH TECHNIQUE – BASICS OF THE GROWTH TECHNOLOGY AND PROPERTIES OF THE LAYERS - Zytkiewicz, Zbigniew (Latakia University Journal -Basic Sciences Series, 2018)
This article provides a general review of the epitaxial lateral overgrowth (ELO) technology and of application of ELO layers as substrates with adjustable value of lattice constant. In particular, the issues of ELO growth mechanism, substrate defect filtration during ELO procedure and strain in ELO layers will be addressed. Literature data on MOVPE and HVPE ELO growth of GaN on sapphire and our results on lateral overgrowth of III-V structures (GaAs/GaAs, GaAs/Si, GaSb/GaSb, GaSb/GaAs, etc.) by LPE are used as examples. Other lateral overgrowth techniques (LPE growth of lattice mismatched bridge layers and pendeo-epitaxy) will also be shortly presented and compared with the conventional ELO technique.